THE DESIGN OF MOBILE LEARNING APPLICATION ABOUT ISLAMIC CULTURE AL HISTORY ON ANDROID SMARTPHONE - Yaya Hidayat (NUANSA INFORMATIKA, 2016)
The development of technology on mobile phones is now developed by using Android operating system technology. Android is an operating system for mobile phones based on Linux operating system that is Open Source. With today's mobile technology, we can easily use it as one tool that can help in everyday life. Mobile phone can be used as a fun learning media, it is well known as Mobile Learning (m-Learning). Mobile Learning is the next generation of e-Learning and based on mobile devices. Mobile learning is a learning model that utilizes information and communication technology. In the application that the author created contains about complementary means of learning systems to support especially on the history of Islamic culture that is knowledge about the history of Islam. Which is presented using the tools of mobile and android technology where students can get the material, working on the matter gets the value. with media aids such as android based smartphones. This application may be helpful for students in MTsN Kadugede in studying Islamic cultural history.Keywords: Android, Mobile Learning, smartphone, History of Islamic Culture